'The best thing since sliced bread': Patient experiences of teleoncology in western NSW. (2nd September 2022) - Pye, Sid; Webster, Emma; Zielinski, Rob; Honeyball, Florian
Abstract: Objective: This study explored experiences of rural cancer patients who were receiving treatments by remote video‐assisted chemotherapy (RVAC) or participating in clinical trials remotely. Setting: Participants lived in Coonabarabran or Dubbo in western NSW. Participants: Seven cancer patients undergoing treatment for breast, bladder or colon cancer, renal cell carcinoma or lymphoma. Design: Appreciative inquiry informed this qualitative study. Semi‐structured interviews were conducted between July 2018 and January 2019 and thematically analysed. Results: The patient experience of teleoncology was overwhelmingly positive. Patients explained the value of relationships that developed with the local and virtual care team. Patients felt they received better care if they saw the same oncologist for the duration of their treatment and felt RVAC had accommodated this. Teleoncology allowed patients to remain independent because they were able to maintain their usual support mechanisms including family, friends and health care team. Patients described the reduced physical and emotional travel burden in addition to reduction in travel time and cost. Conclusions: These findings highlight the acceptability of teleoncology for rural patients as chemotherapy can be added to the health care and social and emotional supports, which exist in their hometown. Expansion of teleoncology should be codesigned with local communities with a focus on establishing care teams with consistent staffing to build trust between the treating team and the patient. These relationships improve the patient experience and enhance patient independence, which is a desirable attribute of cancer survivorship. Recruitment to clinical trials using teleoncology is acceptable and should be factored into trial development.